2021
DOI: 10.1155/2021/7866720
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Keap1/Nrf2 Signaling Pathway Significantly Promotes the Progression of Type 1 Diabetes Mellitus

Abstract: Type 1 diabetes mellitus (T1DM) is an autoimmune disease characterized by insulin deficiency due to pancreatic β-cell damage and leads to hyperglycemia. The precise molecular mechanisms of the etiology of T1DM are not completely understood. Oxidative stress and the antioxidant status of pancreatic β-cells play a vital role in the pathogenesis and progression of T1DM. The Keap1/Nrf2 signaling pathway plays a critical role in cellular resistance to oxidative stress. This study is aimed at investigating the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This dysmetabolism is also associated with oxidative stress. A recent study has demonstrated that the inhibition of Nrf2 signalling could significantly promote the incidence of type I diabetes mellitus, and, on the other hand, its reactivation reduces oxidative stress in pancreatic β-cells [ 143 ]. At the same time, the absence of Nrf2 protects from insulin resistance in long-term high-fat diet feeding by decreasing adipose tissue inflammation [ 144 , 145 ].…”
Section: Nrf2 Activation As a Strategy For Covid-19 Treatmentmentioning
confidence: 99%
“…This dysmetabolism is also associated with oxidative stress. A recent study has demonstrated that the inhibition of Nrf2 signalling could significantly promote the incidence of type I diabetes mellitus, and, on the other hand, its reactivation reduces oxidative stress in pancreatic β-cells [ 143 ]. At the same time, the absence of Nrf2 protects from insulin resistance in long-term high-fat diet feeding by decreasing adipose tissue inflammation [ 144 , 145 ].…”
Section: Nrf2 Activation As a Strategy For Covid-19 Treatmentmentioning
confidence: 99%
“…Similarly, obese patients exhibit a lower degree of activated Nrf2 transcription factor [129] . Attesting to its pathological importance, a recent study demonstrated that inhibition of the Keap1/Nrf2 signalling pathway promotes incidence of diabetes mellitus (DM), and conversely, activation reduces oxidative stress in pancreatic β-cells [130] . Endothelial cell dysfunction and thrombosis are cardinal signs of severe COVID-19 [131] , while activation of Nrf2 protects the endothelium from oxidative stress and cytokine storm [132] .…”
Section: Oxidative Stress As a Potential Therapeutic Targetmentioning
confidence: 99%
“…These phenomena occur in parallel after cumulative oxidative stress reaches a certain threshold ( 66 ). In T1D, ROS promote autoimmune responses, cytokine release, and inflammation-induced impairment of β-cell function ( 70 ). Drews et al suggested that oxidative stress-mediated loss of cellular function (e.g.…”
Section: β-Cell Dedifferentiationmentioning
confidence: 99%